Pemanfaatan Media Canva Pada Mata Pelajaran Pendidikan Agama Islam Di Sekolah Menengah Pertama - Suriyati, Suriyati; Abubakar, Abubakar; Nur, Taufiq; Swito, Agus; Nuraeni, Nuraeni (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2024)
This research aims to find out how canva media is used in PAI subjects at SMPN 5 Sinjai. This type of research is qualitative research. The subjects in this research are educators and students who apply technology-based learning tools, for example the canva application. The data collection methods are observation, interviews and documentation, while the data analysis techniques are data reduction, data presentation and data verification. The results of this research found that the use of the canva application in PAI subjects had a positive impact where the use of the canva application could increase students' interest in the subject matter, make understanding more interesting, and be able to increase learning concentration. Using the canva application can make students more focused on delivering material, increase students' enthusiasm and motivation during learning and make learning less boring, making students less sleepy so that it can increase students' understanding. Apart from that, the canva application makes it easier for teachers to create interesting teaching media